Analysis of the Use of Digital Puzzle Media on Elementary School Student’s Learning Motivation (Case Study of 3rd Grade Students at SDN 1 Sajen Academic Year 2025/2026) - Dewi, Sri Candra; Riyadi, Riyadi; Chumdari, Chumdari; Suryandari, Kartika Chrysti; Salimi, Moh (Universitas Sebelas Maret, 2026)
This study addresses the limited use of instructional media by elementary school teachers in fostering students’ learning motivation in Science subjects. The purpose of this study is to analyze the use of digital puzzle media in enhancing students’ learning motivation. This research employed a qualitative approach with a case study design conducted at SD N 1 Sajen. The participants consisted of 31 third-grade students, including 19 boys and 12 girls. The findings show that digital puzzle media effectively increase students’ motivation and enthusiasm in Science learning. Observation and documentation results indicate that the media attract students’ attention and encourage active participation during the learning process. In addition, interviews reveal that students feel more enthusiastic and engaged when learning using digital puzzle media. In conclusion, digital puzzle media can foster elementary school students’ learning motivation in Science subjects and support more interactive and engaging learning experiences.